Causes of visits to outpatient pediatric clinic at University Children’s Hospital of Lublin in 2004-2006 - Płowaś-Goral, Małgorzata; Chemperek, Ewa; Kucmin, Tomasz; Szwarc, Paweł; Nogalski, Adam (Polish Journal of Public Health, 2010)
Aim. The aim of the study was to analyze the structure of visits to the Outpatient Pediatric Clinic at the University Children’s Hospital of Lublin. Material and methods. Seven main reasons for a visit to the outpatient pediatric clinic were identified: surgical illnesses, trauma, burns, road traffic accidents, pediatric illnesses, otolaryngological illnesses and poisoning. Results. Within the analyzed period of time a general increase in the number of visits to the outpatient clinic was observed. The most frequent principal reasons for visit were surgical illnesses (44.3% of all the recorded visits). The number of such visits in the analyzed period of time was systematically increasing, and there were 23 surgical visits per day on average. The second most frequent reasons for visit to outpatient pediatric clinic were pediatric illnesses (29.2% of all the recorded visits) and the average number of such visits per day was 15. The average number of visits due to all the reasons listed above within a 24-hour period was the highest on Saturdays and the lowest on Thursdays. Regardless the year and the reason, visits to the pediatric outpatients clinic were most frequent in May and June and least frequent in July and August.